СУСПІЛЬНА НЕБЕЗПЕКА ДІЯНЬ, ПОВ’ЯЗАНИХ ІЗ СЕКСУАЛЬНОЮ ЕКСПЛУАТАЦІЄЮ ДИТИНИ - Мискова, Ганна Миколаївна (SUPREMANCE OF LAW, 2019)
The article deals with the issues of public danger and criminal analysis of actions related to sexual exploitation of a child. The crimes related to the sexual exploitation of children have been divided into three groups of socially dangerous acts: preceding sexual exploitation (Article 149 of the Criminal Code of Ukraine); that constitute the purpose of sexual exploitation (Articles 301-303 of the Criminal Code of Ukraine); related to sexual violence, as well as other crimes against sexual freedom and the integrity of the child (Articles 152-156 of the Criminal Code of Ukraine).